Pendampingan dan Peningkatan Kualitas Rumah Data Kependudukan dan Informasi Keluarga di Kampung KB Akrab Kelurahan Tingkir Lor Kota Salatiga Tahun 2022 - Daru Purnomo; Sally Agustina Raung; Shela Yonanda; Richard Hartono Wijaya; Auria Rizqi Amelia; Nilam Puteri Anggini Ratulia (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2022)
The House of Population Data and Family Information is a community activity group (poktan) that carries out activities for collecting, verifying, analyzing, presenting, utilizing population data and family information as well as development at the village/ward level or commonly referred to as my data house. Skopa Rumah Dataku Tingkir Lor is currently at the RW level where the availability of data houses physically and administratively does not meet the proper qualifications. In the Institutional Practice Lecture or KPK activities carried out by several students from Satya Wacana Christian University in the Tingkir Lor Village, it is hoped that this will help fulfill the classification of data houses both physically and administratively. The efforts given starting from data collection, verification, data input to data presentation have been submitted to Rumah DataKu.